The Feasibility of Coin Motors for Use in a Vibrotactile Display for the Blind. Issue 6 (13th January 2015) - Stronks, H. Christiaan; Parker, Daniel J.; Walker, Janine; Lieby, Paulette; Barnes, Nick
Abstract We have tested the potential of three types of vibration motors for use in a tactile vision substitution device for the blind. The motors were of the coin type, which are available off‐the‐shelf, and are characterized by their affordability, energy efficiency, and ease of implementation. The primary limitation of coin motors is the lack of control they offer over stimulus parameters. Specifically, adjusting the input voltage of a coin motor not only changes the vibration intensity, but also the vibration frequency and duration. This characteristic may result in unpredictable perceptions in psychophysical tests. By using standard psychophysical procedures, we were able to show that the tested coin motors evoked predictable magnitude perceptions across their dynamic range, following Fechner's law as if vibration intensity alone were varied. The best‐performing motor was able to generate a median number of 15 available just‐noticeable differences, meaning that it was potentially capable of conveying 16 gray levels in its dynamic range. We conclude that coin motors are potential candidates for the construction of a tactile display to substitute for lost vision.